FMD and CIMT: Surrogate markers of atherosclerosis in subclinical and overt hypothyroidism in sub Himalyan Region - Bandana Kumari (Wolters Kluwer Medknow Publications, 2021)
Introduction: Hypothyroidism increases the risk of atherosclerosis. Carotid intima-media thickness (CIMT) and flow-mediated dilation (FMD) have been used as a noninvasive method to detect atherosclerosis. But the literature is scarce on patients with subclinical hypothyroidism. Such a study was not done in our region, so we conducted this study at a tertiary care center to compare CIMT and FMD among subclinical and overt hypothyroid patients and to analyze the risk of atherosclerosis. Methods: We evaluated 68 patients aged 18–50 years, with newly diagnosed hypothyroidism. We divided them into overt and subclinical hypothyroidism groups and compared the findings. All analyses were performed by the computerized SPSS 17.0. The results were noted as means ± SD and percentage. Student's t-test was used to compare continuous variables, and the Chi-square test was used to compare differences. Results: The total number of patients with dyslipidemia in the subclinical hypothyroidism (SCH) group was 22 (45.83%) and in the overt hypothyroidism (OH) group was 26 (54.16%) with a P- value of 0.009. The mean FMD% in subclinical hypothyroidism patients was 6.9816 ± 3.4224 and in overt hypothyroidism patients was 5.3670 ± 2.7278 (P = 0.03). The mean CIMT was 0.5009 ± 0.0732, CIMT in the SCH group was 0.5082 ± 0.0672 and in the OH group was 0.5305 ± 0.0799 (P = 0.2). Conclusion: The outcome of this study specifies that hypothyroidism is associated with endothelial dysfunction as established by impaired FMD, and it may be the first marker of atherosclerosis appearing before any structural evidence like CIMT. We can speculate that there is a link between subclinical hypothyroidism and atherosclerosis, and thyroxine replacement in SCH may help to prevent the progression of atherosclerosis.